PERLINDUNGAN HUKUM TERHADAP DEBITUR DALAM PINJAM MEMINJAM UANG YANG BERBASIS ONLINE - Ida Bagus Gilang Paramartha; Aris Munandar; Muhammad Sood (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The purpose of this research is to find out legal relationship regarding the rights and obligations of the parties in carrying out online-based lending and borrowing agreements and to find out the legal settlement in the event of a default in the online lending and borrowing implementation. The approaches used in this research are: the statute approach, the conceptual approach, the Historycal Approach, and all of the data were collected using literature study techniques and analyzed normatively. the provisions of the online-based lending and borrowing agreement cannot be separated from the legal terms of the agreement in Article 1320 of the Civil Code, besides that in practice the parties also adhere to Article 1338 of the Civil Code which makes the agreement a legal basis for them and POJK Number 77/POJK.01 /2016. Legal protection for parties in the implementation of online-based lending and borrowing includes preventive legal protection as well as repressive legal protection. In the legal relationship of the parties, if there is a default or dispute, the parties in the event of a default or dispute, the parties can resolve it in two ways, namely through litigation and non-litigation